Blood Oxygenation Level Dependent Activation in Basal Ganglia Nuclei Relates to Specific Symptoms in De Novo Parkinson's Disease - Prodoehl, Janey (2010)
To aid the development of symptomatic and disease modifying therapies in Parkinson's disease (PD), there is a strong need to identify non-invasive measures of basal ganglia function that are sensitive to disease severity. This study examines the relation between blood oxygenation level dependent (BOLD) activation in every nucleus of the basal ganglia and symptom-specific disease severity in early stage, de novo PD. BOLD activation measured at 3 Tesla was compared between 20 early stage de novo PD patients and 20 controls during an established precision grip force task. In addition to the basal ganglia nuclei, activation in specific thalamic and cortical regions was examined. There were three novel findings. First, there were significant negative correlations between total motor Unified Parkinson's Disease Rating Scale (UPDRS) and BOLD activation in bilateral caudate, bilateral putamen, contralateral external segment of the globus pallidus, bilateral subthalamic nucleus, contralateral substantia nigra, and thalamus. Second, bradykinesia was the symptom that most consistently predicted BOLD activation in the basal ganglia and thalamus. Also, BOLD activation in the contralateral internal globus pallidus was related to tremor. Third, the reduced cortical activity in primary motor cortex and supplementary motor area in de novo PD did not relate to motor symptoms. These findings demonstrate that BOLD activity in nuclei of the basal ganglia relates most consistently to bradykinesia. The findings demonstrate that functional magnetic resonance imaging has strong potential to serve as a non-invasive marker for the state of basal ganglia function in de novo PD.